WORD EDUCATIONAL SEMANTICS OF COMPOSERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Concepts and terms “Composite” and “Compound word” were separated. System description of ways of Russian synchronic composites-building with consideration of possibility of primary and secondary composites appearance was made, Specific, formal and semantic indications of different forms and types composites were found.